The Christological Assimilation of the Apocalypse: An Essay on Fundamental Eschatology. By Paul O’Callaghan - Jones, Ivor H. (The journal of theological studies, 2007)
The argument of the author is that eschatology in the New Testament material is an explication of Christian soteriology, a working out of the salvation won for humanity in Christ. Such a definition is seen as an improvement on both the thorough-going apocalyptic and the originally realized (or existentialist or performative) eschatologies of New Testament scholars (the author might note that C. H. Dodd was a Congregationalist, and not an Anglican!), and on what is described as the ‘agnostic eschatology’ of some modern theologians.